2003
DOI: 10.1037/0097-7403.29.3.184
|View full text |Cite
|
Sign up to set email alerts
|

Abstract-concept learning and list-memory processing by capuchin and rhesus monkeys.

Abstract: Three capuchin monkeys (Cebus apella) touched the lower of 2 pictures (same) or a white rectangle (different), increased same/different abstract-concept learning (52% to 87%) with set-size increases (8 to 128 pictures), and were better than 3 rhesus monkeys (Macaca mulatta). Three other rhesus that touched the top picture before choices learned similar to capuchins but were better at list-memory learning. Both species' serial position functions were similar in shape and changes with retention delays. Other spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
85
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 51 publications
2
85
0
Order By: Relevance
“…These more recent experiments have shown that experience with several examples of same/different relations increases the tendency of pigeons and both old-and new-world monkeys to transfer that training to new stimuli (Katz, Wright, & Bachevalier, 2002;Wright et al, 1988;Wright, Rivera, Katz & Bachevalier, 2003). However, no such constraint or limitation of stimulus set size seems to hold for chimpanzees (Oden, Thompson, & Premack, 1988).…”
Section: Same/different Learningmentioning
confidence: 96%
“…These more recent experiments have shown that experience with several examples of same/different relations increases the tendency of pigeons and both old-and new-world monkeys to transfer that training to new stimuli (Katz, Wright, & Bachevalier, 2002;Wright et al, 1988;Wright, Rivera, Katz & Bachevalier, 2003). However, no such constraint or limitation of stimulus set size seems to hold for chimpanzees (Oden, Thompson, & Premack, 1988).…”
Section: Same/different Learningmentioning
confidence: 96%
“…This approach to studying abstract-concept learning is supported by positive transfer results from phylogenetically diverse species which were once thought to be incapable of S/D abstract-concept learning (i.e., a qualitative absence in this cognitive module), including language-naïve chimpanzees (Thompson, Oden, & Boysen, 1997), baboons (Bovet & Vauclair, 2001), capuchin monkeys (Wright, Rivera, Katz, & Bachevalier, 2003), rhesus monkeys (Wright, Santiago, Urcuioli, & Sands, 1984), parrots (Pepperberg, 1987), and pigeons . Additional studies have found evidence consistent with S/D abstract-concept learning, however, due to procedural limitations, the results are open to alternative explanations.…”
mentioning
confidence: 94%
“…During Phase 1, a requirement of three touches of the sample was implemented to promote better control by the sample (Wright, Rivera, Katz, & Bachevalier, 2003). A change from a 0 to 1 s delay was introduced to avoid accidental touches recorded as incorrect choices.…”
Section: Studymentioning
confidence: 99%